2003
DOI: 10.1063/1.1572192
|View full text |Cite
|
Sign up to set email alerts
|

Be diffusion in molecular beam epitaxy-grown GaAs structures

Abstract: Beryllium diffusion is considered in heavily doped p-type GaAs structures grown by molecular beam epitaxy (MBE). Secondary ion mass spectrometry (SIMS) measurements performed on samples which underwent rapid thermal processing (RTP) experiments at 850 °C for 30 s show that (i) Be diffusion is faster in p/p+/p structures than in p/p+ ones and (ii) an increase of the As4/Ga flux ratio during the MBE growth affects Be diffusion only in p/p+ structures. These results are discussed by modeling Be diffusion accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…The suggested states varied from neutral 4 , to +1 5,6,7 , +2 8,9,10 , or both +2 and +3 11,12 . Recently, however, Bracht et al 1 found that fits of recent as well as earlier diffusivity profiles are more accurate for dominant neutral and +1 charge states.…”
Section: Introductionmentioning
confidence: 99%
“…The suggested states varied from neutral 4 , to +1 5,6,7 , +2 8,9,10 , or both +2 and +3 11,12 . Recently, however, Bracht et al 1 found that fits of recent as well as earlier diffusivity profiles are more accurate for dominant neutral and +1 charge states.…”
Section: Introductionmentioning
confidence: 99%
“…As it is known, high beryllium doping of heterojunctions results in considerable Be diffusivity all along the differently doped layers [8]. For sample S940, higher Be-diffusion could be expected as compared to S1000 due to the larger doping mismatch between the GaAs and AlGaInP layers (3 Â 10 19 and 1:1 Â 10 18 ; respectively).…”
Section: Resultsmentioning
confidence: 97%
“…The studies of the formation energy of the Ga self-interstitials in GaAs have shown that their charge state can be +1 [20], +1 or +3 [21], +1 and +2 and +3 [22]. In this way, the singly [5,9,10] and doubly [7,8,11] positively charged Ga interstitial point defects were used in kick-out models of Be diffusion in GaAs. Some authors have employed the neutral Ga selfinterstitials in their corresponding models [4,6].…”
Section: Resultsmentioning
confidence: 99%
“…From the studies of Be diffusion near the p-n junctions [6] as well as the concentration dependence of Be diffusivity [16,17] and also from the simulations [4,5,[9][10][11], the values of 0 [4,16] and +1 [5,6,[9][10][11]17] have been proposed for Be interstitial charge state.…”
Section: Resultsmentioning
confidence: 99%